A possible primary cause of cancer: deficient cellular interactions in endocrine pancreas - Israël Maurice (Molecular Cancer, 2012)
Abstract Background Cancer is a devastating type of disease. New and innovative ways to tackle cancers that have so far proved refractive to conventional therapies is urgently needed. It is becoming increasingly clear that, in addition to conventional therapeutics targeting by small molecules, that tumor cell metabolism presents new opportunities to target selectively specific cancer cell populations. Metabolic defects in cancer cells can be manifested in many ways that might not be readily apparent, such as altering epigenetic gene regulation for example. The complex rewiring of metabolic pathways gives tumor cells a special advantage over differentiated cells, since they deplete body stores as fuel for their growth and proliferation. Tumor metabolism looks simpler when we consider that some enzymatic switches are in a neoglucogenic direction thereby depleting body stores. However, these pathways may be inadequately switched on by catabolic hormones (glucagon, epinephrine and cortisol) in a specific situation where anabolism is activated by, for example insulin released from beta pancreatic cells or IGF, inducing mitosis and synthesis that are powered by glucose catabolism. Such a hybrid metabolic situation would be reached if a pancreatic beta cell mechanism, mediated by GABA, failed to silence neighboring alpha cells and delta cells. The inhibitory transmitter GABA hyperpolarizes alpha and delta cells via their GABA A receptors, and blocks the release of glucagon and somatostatin. Alternatively, an anomaly of alpha cell channels, would lead to a similar situation. Whatever is the alteration, anabolism fails to silence catabolism and enzymatic switches controlled by kinases and phosphatases adopt an inadequate direction, leading to a hybrid metabolic rewiring found in cancer. It is daring to formulate such a hypothesis as this. However, it is quite possible that the starting point in cancer is an alteration of the endocrine pancreas, suppressing the mechanism by which beta cells silence the neighboring alpha and delta cells, with GABA and Zn2+.